OPTIMIZING PRODUCTIVE LAND WAQF TOWARDS FARMERS PROSPERITY - Puspitasari, Ajeng Wahyu (Journal of Indonesian Applied Economics, 2017)
Data of The Ministry of Religion of Indonesia show that the total number of land waqf is 4,359 billion M2 in Indonesia (data of March, 2016). Based on this data, land waqf has a huge potential economics to be improved in Indonesia as community economic development. Land waqf, generally, is used to built a mosque, orphanage, and other public facilities. On the other side, the development of agriculture getting decrease because being converted into residence, especially in Indonesia as the agraris country. The use of land waqf is not maximum yet, therefore we have a big chance to cultivate the land waqf by using an Islamic concept of agriculture as one of the solution.            Realizing the importance of land waqf management, this study aims ensuring that land waqf can be managed by the local government and to be used as farmland by involving farmers as workers investigating  by using a literature review. The concept of land waqf is muzara'ah, there is an agreement between the local governance (as the manager of land waqf) and farmers (as the workers) to cultivate the land, then at the end of this agreement, the total yield will taken by the local government in order to fulfill the needs of the farmers. Optimizing the potential of land waqf in Indonesia, in order to reach the maximum benefit of waqf that called as falah.